"Digital Lives in the Global City: Contesting Infrastructures", edited by Deborah Cowen, Alexis Mitchell, Emil Paradis, and Brett Story. Vancouver: University of British Columbia Press, 2020. - Niccolò Morelli (Partecipazione e Conflitto, 2023)
For Book Reviews Abstract is not mandatory